The Effect of Beneficiation on Some Properties of Osun State Ceramic Raw Materials - Abiola, Oluranti Adetunji; Oke, Adekola Olayinka; Omidiji, Babatunde Victor; Adetan, Dare Aderibigbe (Journal of Casting & Materials Engineering, 2019)
Clay, feldspar and silica sand are important industrial minerals which often need treatment commonly known as beneficiation to improve the quality of ceramic tiles produced from these materials. The different minerals, after sorting, were treated separately in distilled water, alcohol and hydrochloric acid before being crushed in a ball mill; they were then characterized using a pelletron accelerator. The results show an increased silicon content for clay, silica sand and feldspar; and reduced aluminum content for clay and silica sand but not for feldspar. Iron impurity and its oxide are also shown to reduce by over 50% in all the minerals while potassium was found to be the dominant element in feldspar among the defining elements. In conclusion, the increased quartz in the mineral will improve the hardness, density, porosity, and rigidity of ceramic tiles as well as providing support and controlling shrinkage. Furthermore, increasing the mineral quotient in feldspar will enhance its fluxing potential.